2022
DOI: 10.3389/fimmu.2022.829943
|View full text |Cite
|
Sign up to set email alerts
|

Killer Cell Immunoglobulin-Like Receptor Haplotype B Modulates Susceptibility to EBV-Associated Classic Hodgkin Lymphoma

Abstract: Tumor cells of classic Hodgkin lymphoma (cHL) are derived from antigen presenting B cells that are infected by Epstein Barr virus (EBV) in ~30% of patients. Polymorphic Killer cell immunoglobulin-like receptors (KIRs) expressed on NK cells interact with human leukocyte antigen (HLA) class I and play a key role in immune surveillance against virally infected cells and tumor cells. We investigated the effect of KIR types on cHL susceptibility overall (n=211) and in EBV-stratified subgroups using the Dutch GoNL c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Further, multiple candidate gene case/control studies have found associations between KIR polymorphism and EBV infection and complications (Besson et al 2007 ; Durovic et al 2013 ; Gao et al 2015 ; Huo et al 2015 ; Kovacic et al 2005 ; Qiang et al 2012 ). Although not altogether consistent in associations, these studies tend towards the finding that activating KIR underlie susceptibility to NPC, BL, and EBV-HLH (Huo et al 2015 ; Kovacic et al 2005 ; Muriuki et al 2021 ; Nowak et al 2019 ; Qiang et al 2012 ), although protective against HL (Besson et al 2007 ; Jiang et al 2022 ). Interestingly, while the A*11:01 allotype is protective from NPC, A*11:02, which differs by one amino acid that results in productive KIR binding, is not and is associated with NPC in a KIR-dependent manner (Gao et al 2017 , 2015 ; Graef et al 2009 ).…”
Section: Hla Alleles and Their Receptors Coordinate Variable Immune R...mentioning
confidence: 99%
“…Further, multiple candidate gene case/control studies have found associations between KIR polymorphism and EBV infection and complications (Besson et al 2007 ; Durovic et al 2013 ; Gao et al 2015 ; Huo et al 2015 ; Kovacic et al 2005 ; Qiang et al 2012 ). Although not altogether consistent in associations, these studies tend towards the finding that activating KIR underlie susceptibility to NPC, BL, and EBV-HLH (Huo et al 2015 ; Kovacic et al 2005 ; Muriuki et al 2021 ; Nowak et al 2019 ; Qiang et al 2012 ), although protective against HL (Besson et al 2007 ; Jiang et al 2022 ). Interestingly, while the A*11:01 allotype is protective from NPC, A*11:02, which differs by one amino acid that results in productive KIR binding, is not and is associated with NPC in a KIR-dependent manner (Gao et al 2017 , 2015 ; Graef et al 2009 ).…”
Section: Hla Alleles and Their Receptors Coordinate Variable Immune R...mentioning
confidence: 99%
“…[100][101][102] Of these, Epstein-Barr virus (EBV) likely has the greatest impact on human health, 103 and specific combinations of KIR with HLA class I ligand allotypes can influence whether an EBV infection is controlled or leads to complication. [104][105][106][107] Importantly, specific pathogen infections can leave an imprint on NK cell clonal diversity and receptor expression, with implications for subsequent maintenance of homeostasis. 108,109 FIGURE 1.…”
Section: Combinatorial Diversity Of Kir and Hla Class I Influences In...mentioning
confidence: 99%
“…More recent genome wide association analyses (GWAS) have demonstrated in the genetic orchestra predisposing to HL, the implication of a number of genes, with one of the strongest effects played by human leucocyte antigen (HLA) class I loci, followed by genes involved in germinal center reaction, T cell differentiation, NF-κB activation [ 24 ]. Variants in IL13 , GATA3 , HLA class II regulators, Polymorphic Killer cell immunoglobulin-like receptor ( KIR ) haplotypes of group B have been shown strongly associated with EBV-negative HL cases in young adults [ 24 , 25 ], whereas polymorphisms close to HLA class I loci were mostly associated with EBV-positive HL [ 26 ]. Metanalytic HLA imputations from GWAS data showed specific alleles strongly associated with the risk of EBV-positive HL including A*01:01 , C*07:01 , B*08:01 , DRB1*03:01 , DQB1*02:01 , B*37:01 [ 27 ].…”
Section: The Epidemiological Immunogenetic and Environmental Backgrou...mentioning
confidence: 99%